Oral cancer A descriptive study of in-patient cases at the Philippine General Hospital from 2006-2010 - Bare, Joecyl Lloren; Buyawe, Diane Joy G.; Karganilla-Frange, Melanie Ruth (Co-author).; Yumul, Giselle (Adviser).
Current data asserts that socio-demographic factors may play an important role in oral cancer development. Hence, this study aims to describe the socio-demographic profile of Filipino oral cancer patients at the Philippine General Hospital (PGH). Methods: A total enumeration, descriptive study was carried out. Medical records of Filipino patients (115) with oral cancer admitted at the PGH from 2006-2010 were reviewed. Data as to age sex, occupation, location, lifestyle, comorbidities and cancer site and type were noted and analyzed using tables and graphs. Results: The following have the highest percentage in the socio-demographic factors reviewed: males (57%), age range of 51-60 (30%), blue-collar workers (29%), urban dwellers (57%), smoking with alcoholic beverage drinking (28%) and hypertension (195). Among oral cancer types and sites, squamous cell carcinoma and salivary glands accounts for 56% and 33% respectively. Conclusion: The age predilection among the subjects ranges from 51-60 with males being more affected than females. A greater percentage are urban dwellers and blue-collar workers. Smoking with alcoholic beverage drinking was the foremost predisposing lifestyle practice while hypertension was the most commonly seen comorbidity. Finally, squamous cell carcinoma remained the most frequently observed malignancy while salivary glands is the primary site of occurrence.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.